2017
DOI: 10.1371/journal.pone.0173206
|View full text |Cite
|
Sign up to set email alerts
|

On the adhesion-cohesion balance and oxygen consumption characteristics of liver organoids

Abstract: Liver organoids (LOs) are of interest in tissue replacement, hepatotoxicity and pathophysiological studies. However, it is still unclear what triggers LO self-assembly and what the optimal environment is for their culture. Hypothesizing that LO formation occurs as a result of a fine balance between cell-substrate adhesion and cell-cell cohesion, we used 3 cell types (hepatocytes, liver sinusoidal endothelial cells and mesenchymal stem cells) to investigate LO self-assembly on different substrates keeping the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…As we hypothesized that cell encapsulation within microscale droplets could overcome this challenge, we initially modeled oxygen concentration by using COMSOL multiphysics modeling software. We have taken into consideration oxygen diffusion according to Fick's second law and consumption by the cells according to Michaelis–Menten kinetics . The external concentration of oxygen was considered as the concentration within arterial blood and oxygen diffusion coefficient was considered as the one in a muscle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we hypothesized that cell encapsulation within microscale droplets could overcome this challenge, we initially modeled oxygen concentration by using COMSOL multiphysics modeling software. We have taken into consideration oxygen diffusion according to Fick's second law and consumption by the cells according to Michaelis–Menten kinetics . The external concentration of oxygen was considered as the concentration within arterial blood and oxygen diffusion coefficient was considered as the one in a muscle.…”
Section: Resultsmentioning
confidence: 99%
“…We have taken into consideration oxygen diffusion according to Fick's second law and consumption by the cells according to Michaelis-Menten kinetics. [18] The external concentration of oxygen was considered as the concentration within arterial blood and oxygen diffusion coefficient was considered as the one in a muscle. Two assumptions were made during our mathematical modelling: 1) Twenty minutes is considered the maximal period of time, in which cardiac cells can survive without oxygen.…”
Section: Oxygen Diffusion Modelingmentioning
confidence: 99%
“…Developing physiologically relevant in vitro models to mimic cell and tissue organ response is one of the main challenges in experimental cell biology and tissue engineering. Organoid technology has emerged as a novel method to generate structural and functional tissue models 15,[32][33][34][35] . Luminal organoids were first generated from intestinal stem cells by Clevers and coworkers 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The results are confirmed by experimental studies on liver buds by Ramachandran et al 22 ; the authors found no evidence of cell death in liver buds cultured in well-mixed fluidic bioreactors while those in static conditions developed a necrotic core. Mattei et al 43 demonstrated that the minimum oxygen level in liver buds with an average mass of a few mg cultured in bioreactors is 0.04 mol/m 3 , compared with 0.01 mol/m 3 in static culture plates. As shown in Table 4, the gel-free structures resembling liver buds maintain the criteria of quarter power scaling (b ≈ -1/4) and viable oxygen concentrations only if their radii are maintained in a narrow range (between 654 and 712 µm in the models).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation